Secondary childhood glaucoma in neurofibromatosis type 1: an unusual corneal leukoma case report - Ge, Ling Ying; Tian, Xin; Guo, Han Mu; Yin, Xue (Frontiers in Oncology, 2024)
Neurofibromatosis type 1 (NF1) is a rare autosomal dominant disorder that affects the skin, eyes and peripheral nervous system. It is rarely associated with glaucoma, especially in pediatric patients. We herein report an unusual case of corneal degeneration in a child with NF1, characterized by peripheral corneal leukoma and a membrane under Descemet’s membrane. This finding offers new insights for the ophthalmic diagnosis of NF1.